ACCOUNTING IN THE LAW SCHOOL. - Dohr, James L. (The Accounting Review, 1930)
Abstract Efforts are being made at Columbia University, New York to correlate the subjects on law, economics and business. Efforts are made to introduce the subject of accounting in the law school curriculum. A good deal of difficulty in arriving at any sort of agreement as to what phases of the subject should be taught, what methods should be used, and what the content of the various courses should be is constantly met with. At the present time the Law School is giving a course in accounting as part of its curriculum. In this course the instructor is avoiding the teaching of what may be called the "mechanics" of accounting. In other words, he makes no effort to teach such things as postings, trial balances, etc. The method tentatively adopted is the presentation of problems with accounting data whose solution involves an application of rules of law. The experiment is still too young to permit very definite conclusions as to its usefulness. It is believed however, that the idea is a sound one and that one may take a measure of satisfaction from the fact that the Law School has definitely recognized the necessity of an accounting course.